Penguatan Karakter Kepedulian Sesama untuk Mencegah Perilaku Perundungan di SD - Stevanus, Ivan; Harbelubun, Yohanna Claudia Dhian Ariani; Budhayanti, Clara Ika Sari (Institute for Research and Community Services, 2024)
Education plays a role in shaping the character of each student as a provision in socializing and interacting with their environment. Character education is considered the most influential in the progress of a country because through humans with character it will produce human resources who know their identity, form good traits, support creativity, care and build leadership qualities. Character education aims to improve the quality of the implementation and results of education in schools that lead to the achievement of character formation and noble morals. One indicator in character formation is a caring character. A caring character is an attitude that has concern for others and the environment, and helps others who are affected by disasters or misfortunes; besides that, a caring attitude also guides students to be able to understand others by controlling their speech, attitudes, and behavior so as not to offend others and accept the strengths and weaknesses of others. The purpose of this training is to improve the caring character in preventing bullying behavior towards others in Strada Nawar Elementary School students in grades III-VI of elementary school totaling 202 students. This activity is carried out in 3 stages, namely the preparation stage in the form of offline materials; the implementation stage, training is carried out offline for 1 day; the third stage, evaluation of the implementation of training and reporting. The targeted output is a journal article published in an accredited national journal. The training material can be accessed by elementary school students.